Kidney structural characteristics based on a kidney biopsy and contrast‐enhanced computed tomography in healthy living kidney donors. Issue 10 (25th January 2020) - Nielsen, Cecilie M.; Skov, Karin; Buus, Niels H.; Pedersen, Michael; Ibsen, Lotte; Krag, Søren P.; Nyengaard, Jens R.
Abstract: The demands for kidney transplantations are increasing, and so is the number of live kidney donors (LKDs). Recent studies show that LKDs have an increased risk of developing end‐stage renal disease compared with healthy non‐donors. However, the knowledge about factors predicting renal disease in kidney donors is sparse. Some evidence points to increased glomerular sclerosis and kidney fibrosis, as well as a low number of glomeruli as associated with a worse renal outcome. This methodological study investigated that which estimates are obtainable with a standard kidney biopsy taken from the donated kidney during the transplantation, and a standard contrast‐enhanced computed tomography (CT) in kidney donors. CT‐scans were used to obtain total volume of the kidney and kidney cortex using the Cavalieri estimator and 2D‐nucleator. Glomerular number density in the biopsies was estimated by a model‐based method, and was multiplied by total cortex volume in order to estimate the total number of glomeruli in the kidney. Glomerular volume was estimated by the 2D‐nucleator and a model‐based stereological technique. Kidney fibrosis (point‐counting), glomerular sclerosis (evaluation of glomerular profiles), and arteriole dimensions (2D‐nucleator) were also estimated in the biopsy sections from the donated kidney. Various studies have attempted to identify predictors of renal outcome in LKDs. There is no consensus yet, and further studies are needed to elucidate if and how the estimates described in this study are associated with renal outcome in LKDs.